Ternary positive electrode material and lithium ion battery and battery module thereof

By using a special ternary positive electrode material in lithium batteries, through particle size control and doping elements, the problems of overheating and ignition of lithium batteries during overcharge tests are solved, and the overcharge test pass rate and battery module are improved. Security.

CN119181782APending Publication Date: 2024-12-24EVE ENERGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411018058.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing lithium batteries and battery modules are prone to overheating, short circuit and fire during overcharge testing, and the positive electrode material has a great impact on overcharge performance. How to improve the overcharge test pass rate is the need of technicians.

Method used

Using ternary positive electrode material, by controlling the particle size and proportion of ternary material A and ternary material B, the ternary material B with a smaller particle size is filled in the gap of larger ternary material A to reduce the ratio Surface area, reduce the contact interface between the electrolyte and the positive electrode material, set up an alumina cladding layer and introduce doping elements, optimize structural stability and sphericality, and improve overcharge stability.

Benefits of technology

It effectively reduces the risk of overcharge side effects, improves the overcharge test pass rate of batteries and battery modules, and ensures stability and safety performance at high voltages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004966992380000111
    Figure BDA0004966992380000111
  • Figure BDA0004966992380000121
    Figure BDA0004966992380000121
Patent Text Reader

Abstract

The invention provides a ternary positive electrode material and a lithium ion battery and a battery module thereof. The ternary positive electrode material comprises a ternary material A and a ternary material B, the particle size D50 of the ternary material A is 12 [mu] m-15 [mu] m, the ternary material A is secondary particles, the particle size D50 of primary particles of the ternary material A is 700 nm-800 nm, the particle size D50 of the ternary material B is 2 [mu] m-5 [mu] m, the ternary material B is monocrystal-like particles, and the particle size D50 of primary particles of the ternary material B is 300 nm-500 nm; the mass ratio of the ternary material A to the ternary material B is (80-90): (10-20). By controlling the particle size of the ternary material A and the primary particle size of the ternary material A and the particle size of the ternary material B and the primary particle size of the ternary material B and mixing the ternary material A and the ternary material B according to a specific proportion, the specific surface area of the ternary positive electrode material is reduced, so that the ternary positive electrode material can maintain excellent overcharge stability and safety performance under high voltage; therefore, the over-charge test passing rate of the battery and the battery module is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular, relates to a ternary positive electrode material and a lithium-ion battery and a battery module thereof. Background Art

[0002] Overcharge test is an important test item to ensure the safety of batteries or battery modules. It is to input voltage and current exceeding the normal standard during the charging process to detect the thermal runaway ability of batteries and battery modules. However, during the overcharge test, batteries and battery modules may overheat, short-circuit, or even catch fire.

[0003] The positive electrode material greatly affects the overcharge performance of batteries and battery modules. For example, Tobishim et al. compared the overcharge performance of aluminum-shell square batteries with LiCoO2 as the positive electrode material in the prior art. The research results show that the battery will explode when charged to a voltage of 10V at a current of 2C. Therefore, how to provide a positive electrode material to improve the overcharge test pass rate of batteries and battery modules is a technical problem that technicians in this field need to solve urgently in their research. Summary of the invention

[0004] The object of the present invention is to provide a ternary positive electrode material and a battery and a battery module thereof, wherein the battery and the battery module have a high overcharge test pass rate.

[0005] According to one aspect of the present invention, a ternary positive electrode material is provided, including ternary material A and ternary material B; the particle size D50 of ternary material A is 12μm~15μm, ternary material A is a secondary particle, the particle size D50 of the primary particle of ternary material A is 700nm~800nm, the particle size D50 of ternary material B is 2μm~5μm, ternary material B is a quasi-single crystal particle, and the particle size D50 of the primary particle of ternary material B is 300nm~500nm; the mass ratio of ternary material A to ternary material B is 80~90:10~20. The particle size D50 of ternary material A can be 12μm, 13μm, 14μm, 15μm, etc., but is not limited to the listed values. Other values ​​not listed in this numerical range are also applicable. The particle size D50 of primary particles of ternary material A can be 700nm, 750nm, 800nm, etc., but is not limited to the listed values. Other values ​​not listed in this numerical range are also applicable. The particle size D50 of ternary material B can be 2μm, 3μm, 4μm, 5μm, etc., but is not limited to the listed values. This numerical range Other unlisted numerical values ​​within the range are also applicable. The particle size D50 of the primary particles of the ternary material B can be 300nm, 350nm, 400nm, 450nm, 500nm, etc., but is not limited to the listed numerical values. Other unlisted numerical values ​​within the numerical range are also applicable. The mass ratio of the ternary material A and the ternary material B can be 80:10, 80:15, 80:20, 90:10, 90:15, 90:20, etc., but is not limited to the listed numerical values. Other unlisted numerical values ​​within the numerical range are also applicable.

[0006] The present invention controls the particle size of ternary material A and its primary particles, the particle size of ternary material B and its primary particles, and mixes ternary materials A and B in a specific ratio, thereby making ternary material B with a smaller particle size easily fill in the gap of ternary material A with a larger particle size, reducing the specific surface area of ​​the ternary positive electrode material, reducing the contact interface between the electrolyte and the ternary positive electrode material, and thus effectively reducing the reaction heat generated by the interfacial reaction between the electrolyte and the ternary positive electrode material, avoiding safety problems such as thermal runaway and gas production caused by overcharge side reactions of the ternary positive electrode material, and ensuring a higher compaction density of the ternary positive electrode material. In summary, the ternary positive electrode material provided by the present invention can maintain excellent overcharge stability and safety performance under high voltage, thereby improving the overcharge test pass rate of batteries and battery modules.

[0007] Specifically, the single-crystal-like particles are composed of one or a few (no more than 5) primary particles, with very few internal grain boundaries; the secondary particles (secondary particle agglomerates) are composed of many primary particles agglomerated, with many internal grain boundaries.

[0008] Preferably, the sphericity of the ternary material A is 0.85 to 0.95. The sphericity of the ternary material A can be 0.85, 0.90, 0.95, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. By using a ternary material A with a specific sphericity, it is beneficial to reduce the specific surface area of ​​the ternary positive electrode material, so that the overcharge stability of the battery and battery module is further optimized.

[0009] Preferably, the surface of the ternary material A is provided with a coating layer, the coating layer includes aluminum oxide, and the aluminum oxide content in the coating layer is not less than 80wt%. The aluminum oxide content in the coating layer can be 80wt%, 85wt%, 90wt%, 100wt%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. By providing an aluminum oxide coating layer on the surface of the ternary material A, the aluminum oxide coating layer serves as a protective layer, which can reduce the direct contact between the positive electrode material A and the electrolyte, reduce the possibility of overcharge side reactions, and thus improve the overcharge stability of the ternary positive electrode material.

[0010] Preferably, the coating layer has a thickness of 6 nm to 10 nm. The coating layer may have a thickness of 6 nm, 7 nm, 8 nm, 9 nm, etc., but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0011] Preferably, the ternary material A comprises a nickel-cobalt-aluminum-lithium ternary material.

[0012] Preferably, the ternary material B includes a nickel-cobalt-aluminum-lithium ternary material.

[0013] Preferably, the chemical formula of the nickel-cobalt-aluminum-lithium ternary material included in the ternary material B is LiNi a Co b Al c M (1-a-b-c) O2, and 0.80≤a≤0.92, 0.062≤b≤0.15, 0.018≤c≤0.05, a+b+c<1, wherein M is a doping element, and the doping element includes at least one of Zr, Mg, and Y. By introducing specific doping elements into the ternary material B, the above-mentioned doping elements are beneficial to improving the internal element distribution of the ternary material B, improving the structural stability of the ternary material B, and reducing the overcharge side reaction activity of the ternary positive electrode material, thereby improving the overcharge test pass rate and electrochemical performance of the battery and battery module.

[0014] Preferably, the preparation method of ternary material B comprises the following operations:

[0015] S2.1 A cobalt-nickel precursor is prepared by a coprecipitation method, and the aging time during the preparation of the cobalt-nickel precursor is 21 to 23 hours; then the nickel-cobalt precursor is sintered at 350 to 450° C. for 4 to 6 hours to obtain nickel-cobalt oxide;

[0016] S2.2: Add lithium source material and aluminum source material to nickel cobalt oxide, first heat to 450-550°C for pre-sintering for 6-8 hours, then heat the mixture to 700-900°C for sintering for 16-20 hours, thereby preparing ternary material B. By reasonably setting the aging time in S1, adopting the segmented sintering method in S2 and controlling the sintering temperature and sintering time, it is beneficial to control the size of ternary material B, thereby reducing the specific surface area of ​​ternary material B.

[0017] Preferably, during the sintering process, the heating rate is not higher than 5°C / min. The above heating rate is conducive to further regulating the particle size of the ternary material B.

[0018] Preferably, the sintering is performed in a nitrogen gas atmosphere, wherein the gas flow rate of oxygen is 20 to 40 mL / min.

[0019] Preferably, the preparation method of ternary material A comprises the following operations:

[0020] S1.1 A cobalt-nickel precursor is prepared by a coprecipitation method, and the aging time during the preparation of the cobalt-nickel precursor is 23 to 25 hours; the nickel-cobalt precursor is then sintered at 350 to 450° C. for 4 to 6 hours to obtain nickel-cobalt oxide;

[0021] S1.2 Add aluminum source material and lithium source material to nickel cobalt oxide, first heat it to 450-550°C and pre-sinter it for 6-8 hours, then heat the resulting mixture to 700-900°C and sinter it for 16-20 hours, thereby obtaining ternary material A.

[0022] Preferably, the sintering is carried out in an oxygen atmosphere, wherein the oxygen gas flow rate is 80-120 mL / min.

[0023] Preferably, during the sintering process, the heating rate is no higher than 5°C / min.

[0024] Preferably, the preparation method of ternary material A also includes the following operations: S1.3 mixing ternary material A with alumina and performing secondary sintering to form a coating layer on the surface of ternary material A, the secondary sintering temperature is 450-550°C, and the time is 12-18 hours.

[0025] According to another aspect of the present invention, a lithium ion battery is provided, comprising a negative electrode sheet and a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating disposed on the surface of the positive electrode current collector, wherein the positive electrode active material contained in the positive electrode active coating comprises the above-mentioned ternary positive electrode material. The lithium battery provided by the present invention has excellent overcharge stability and safety.

[0026] Preferably, in the positive electrode active material contained in the positive electrode active coating, the content of the ternary positive electrode material is not less than 97.9 wt %.

[0027] Preferably, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating disposed on the surface of the negative electrode current collector, the negative electrode active coating comprises a negative electrode active material, the negative electrode active material comprises artificial graphite, the artificial graphite has a graphitization degree of 88% to 91%, an orientation degree OI value ≤6, and a particle size D50 ≤18 μm.

[0028] Specifically, the OI value is the ratio of the peak area of ​​the 004 characteristic diffraction peak to the peak area of ​​the 110 characteristic diffraction peak in the XRD diffraction spectrum of artificial graphite.

[0029] Specifically, the calculation formula of graphitization degree G is: G=[(0.3440-d002) / 0.0086]×100%, where d002 is the (002) crystal plane spacing of artificial graphite, which can be obtained by XRD testing according to the guidance of QJ2507-93, and the unit is nm.

[0030] Preferably, the lithium-ion battery further comprises a diaphragm, and the air permeability of the diaphragm is ≥100s / 100mL.

[0031] Preferably, the lithium-ion battery further comprises an electrolyte, the electrolyte comprises HF, and the content of HF in the electrolyte is ≤0.006wt%.

[0032] According to another aspect of the present invention, a battery module is provided, comprising the above-mentioned lithium-ion battery. The battery module assembled from the above-mentioned lithium-ion battery has a high battery module overcharge test pass rate (2C / 60V) and excellent safety performance. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0034] Example 1

[0035] This embodiment provides a lithium ion battery, and the preparation method thereof is as follows:

[0036] 1. Preparation of positive electrode

[0037] (1) Preparation of ternary material A

[0038] Step S1.1 NiSO4 6H2O and CoSO4 7H2O are mixed in a N2 atmosphere (N2 flow rate 30mL / min) to obtain a 2.0mol / L mixed salt solution, and the mixed salt solution is added to the reactor through a peristaltic pump, the drop rate is 39mL / min, and the feeding time is 30h. Then 4.0mol / L NaOH solution and 1.3mol / L ammonia solution are added to the reactor, and the pH of the reaction solution obtained is controlled to be 11.3, the reaction temperature is 55°C, and the stirring speed is 1100r / min. After the addition is completed, it is aged for 24h, and the obtained precipitate is washed with deionized water several times until neutral, and the nickel-cobalt precursor Ni is obtained after air drying. 0.85 Co 0.15 (OH)2. Weigh the nickel-cobalt precursor Ni 0.85 Co 0.15 (OH)2, sintered at 400℃ in air atmosphere for 5h, and then cooled naturally to obtain nickel-cobalt oxide.

[0039] Step S1.2: Nickel cobalt oxide, lithium source material (LiOH), and aluminum source material (Al2O3) are mixed at a molar ratio of 0.95:1.03:0.05, placed in a tube furnace, and O2 is introduced at a rate of 100 mL / min. The temperature is raised to 500°C at a rate of 2°C / min for pre-sintering for 7 hours. The mixture is then heated to 770°C at a rate of 2°C / min for sintering for 18 hours. After cooling to room temperature, the mixture is taken out to obtain the ternary material A LiNi 0.80 Co 0.15 Al 0.05 O2.

[0040] Among them, the ternary material A is a secondary particle, the particle size D50 of the ternary material A is 13.5 μm, the primary particle size of the ternary material A is 780 nm, and the sphericity of the ternary material A is 0.95;

[0041] Step S1.3: Ternary material A LiNi 0.80 Co 0.15 Al 0.05 O2 and alumina powder are placed in a tube furnace and mixed, O2 is introduced at a rate of 100 mL / min, the temperature is raised to 500°C at a rate of 2°C / min for secondary sintering for 15 hours, and then taken out after cooling to room temperature, thereby forming a coating layer with a thickness of 8 nm on the surface of the ternary material A, which includes Al2O3.

[0042] (2) Preparation of ternary material B

[0043] Step S2.1 NiSO4 6H2O and CoSO4 7H2O are mixed in a N2 atmosphere (N2 flow rate 30mL / min) to obtain a 2.0mol / L mixed salt solution, and the mixed salt solution is added to the reactor through a peristaltic pump, the drop rate is 39mL / min, and the feeding time is 30h. Then 4.0mol / LNaOH solution and 1.3mol / L ammonia solution are added to the reactor, and the pH of the reaction solution obtained is controlled to be 11.5, the reaction temperature is 55°C, and the stirring speed is 1100r / min. After the addition is completed, it is aged for 22h, and the obtained precipitate is washed with deionized water several times until neutral, and the nickel-cobalt precursor Ni is obtained after air drying. 0.85 Co 0.15 (OH)2. Weigh the nickel-cobalt precursor Ni 0.85 Co 0.15 (OH)2, sintered at 400℃ in air atmosphere for 5h, and then cooled naturally to obtain nickel-cobalt oxide.

[0044] Step S2.2: Mix nickel cobalt oxide, lithium source material (LiOH), aluminum source material (Al2O3), and zirconium source material (ZrO2) in a molar ratio of 0.95:1.03:0.05:0.05, place in a tube furnace, introduce N2 at 100 mL / min, heat to 500°C at a rate of 2°C / min, sinter for 7 h, then heat the mixture to 790°C at a rate of 2°C / min, sinter for 18 h, and take out after cooling to room temperature to obtain the ternary material BLiNi 0.80 Co 0.10 Al 0.05 Zr 0.05 O2.

[0045] Among them, the ternary material B is a single crystal-like particle, the particle size D50 of the ternary material B is 3.5 μm, and the primary particle size of the ternary material B is 380 nm.

[0046] (3) Preparation of positive electrode active material

[0047] The above-mentioned ternary material A and ternary material B are mixed in a mass ratio of 85:15 to obtain a ternary positive electrode material NCA, and the ternary positive electrode material NCA is used as the positive electrode active main material of this embodiment.

[0048] (4) Preparation of positive electrode sheet

[0049] 97.9% of the positive electrode active material, 0.9% of the conductive agent SP, and 1.2% of the binder PVDF were mixed evenly and dispersed in NMP to obtain a positive electrode slurry. The positive electrode slurry was coated on aluminum foil, dried at 85°C in a vacuum environment for 24 hours, and then cold pressed and cut to obtain a positive electrode sheet.

[0050] 2. Preparation of negative electrode

[0051] 96.3% of the main active material of the negative electrode, artificial graphite (artificial graphite D50 is 16μm, graphitization degree is 90%, and orientation degree OI value is 8), 1.0% of the conductive agent, 1.5% of the binder and 1.2% of the dispersant are mixed evenly and dispersed in deionized water to prepare the negative electrode slurry. The negative electrode slurry is coated on the copper foil, dried at 100℃ in a vacuum environment for 12h, and then cold pressed and cut to obtain the negative electrode sheet.

[0052] 3. Preparation of electrolyte

[0053] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L, and the electrolyte contains 0.0006% free HF.

[0054] 4. Selection of diaphragm

[0055] A high-pore dynamic diaphragm with an air permeability of 150s / 100mL was used as the diaphragm in this embodiment.

[0056] 5. Assembly and formation of lithium-ion batteries

[0057] The positive electrode sheet, separator and negative electrode sheet are stacked in order, the separator is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell; the bare cell is packaged, injected, left to stand, formed, and divided into different capacities to obtain a lithium-ion battery.

[0058] Example 2

[0059] This embodiment prepares a lithium-ion battery with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is as follows: (1) in the step S1.1 of preparing the ternary material A, the pH value of the reaction solution set in the embodiment 1 is adjusted from 11.3 to 11.5, and in the step S1.2 of preparing the ternary material A, the sintering temperature set in the embodiment 1 is adjusted from 770°C to 750°C; thereby, the particle size D50 of the ternary material A prepared in this embodiment is 12.0 μm, and the particle size D50 of the primary particles of the ternary material A is 700 μm. m; (2) In step S2.1 of preparing ternary material A in this embodiment, the concentration of ammonia solution 1.3 mol / L set in embodiment 1 is adjusted to 1.5 mol / L, and the pH of the reaction solution controlled in embodiment 1 is adjusted to 11.0 from 11.5; thereby, the particle size D50 of ternary material B prepared in this embodiment is 5 μm, and the particle size D50 of primary particles of ternary material B is 500 nm; (3) The mass ratio of ternary material A to ternary material B in the positive electrode active main material used in this embodiment is 80:20. Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in embodiment 1.

[0060] Example 3

[0061] This embodiment prepares a lithium-ion battery with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that: (1) in the step S1.1 of preparing the ternary material A, the pH value of the solution controlled in the embodiment 1 is adjusted from 11.3 to 11.0, and in the step S1.2 of preparing the ternary material A, the sintering temperature set in the embodiment 1 is adjusted from 770°C to 780°C; thereby, the particle size D50 of the ternary material A prepared in this embodiment is 15.0 μm, and the particle size D50 of the primary particles of the ternary material A is 800 μm. m; (2) In step S2.1 of preparing ternary material A in this embodiment, the concentration of ammonia solution 1.3 mol / L set in embodiment 1 is adjusted to 1.0 mol / L, and the pH of the control solution set in embodiment 1 is adjusted to 12.0 from 11.5; thereby, the particle size D50 of ternary material B prepared in this embodiment is 2 μm, and the particle size D50 of primary particles of ternary material B is 300 nm; (3) The mass ratio of ternary material A to ternary material B in the positive electrode active main material used in this embodiment is 90:10. Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in embodiment 1.

[0062] Example 4

[0063] This embodiment refers to the embodiment 1 to prepare a lithium-ion battery. The difference between this embodiment and the embodiment 1 is that in the step S2.2 of preparing the ternary material B in this embodiment, the raw material of the ternary material B does not include the zirconium source material (ZrO2); thus, the ternary material B prepared in this embodiment is LiNi 0.80 Co 0.15 Al 0.05 Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in Example 1.

[0064] Example 5

[0065] This embodiment prepares a lithium-ion battery with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that in the step S2.2 of preparing the ternary material B in this embodiment, nickel cobalt oxide, lithium source material (LiOH), aluminum source material (Al2O3), and magnesium source material (MgO) are mixed in a molar ratio of 0.95:1.03:0.05:0.05; thus, the ternary material B prepared in this embodiment is LiNi 0.80 Co 0.10 Al 0.05 Mg 0.05 Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in Example 1.

[0066] Example 6

[0067] This embodiment prepares a lithium-ion battery with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that in the step S1.3 of preparing the ternary material A, the secondary sintering temperature of 500°C set in the embodiment 1 is adjusted to 550°C, and the secondary sintering time of 15h set in the embodiment 1 is adjusted to 18h; thus, the thickness of the coating layer provided on the surface of the ternary material A prepared in this embodiment is 12nm. Except for the above differences, the materials and process operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0068] Example 7

[0069] This embodiment prepares a lithium-ion battery with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that in the step S1.3 of preparing the ternary material A, the secondary sintering temperature of 500°C set in the embodiment 1 is adjusted to 480°C, and the secondary sintering time of 15h set in the embodiment 1 is adjusted to 12h; thus, the thickness of the coating layer provided on the surface of the ternary material A prepared in this embodiment is 4nm. In addition to the above differences, the materials and process operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0070] Example 8

[0071] This embodiment refers to the preparation of lithium-ion batteries in Example 1. The difference between this embodiment and Example 1 is that this embodiment omits step S1.3, so that the surface of the ternary material A prepared in this embodiment is not provided with a coating layer. In addition to the above differences, the materials and process operations used in this embodiment are strictly consistent with those in Example 1.

[0072] Example 9

[0073] This embodiment prepares a lithium ion battery with reference to the embodiment 1. The difference between this embodiment and the embodiment 1 is that the sphericity of the ternary material A in this embodiment is 0.8. In addition to the above differences, the materials and process operations used in this embodiment are strictly consistent with those in the embodiment 1.

[0074] Comparative Example 1

[0075] This comparative example prepares a lithium-ion battery with reference to Example 1. The difference between this comparative example and Example 1 is that in step S1.1 of preparing ternary material A, the concentration of ammonia solution 1.3 mol / L set in Example 1 is adjusted to 0.9 mol / L, the pH of the reaction solution controlled in Example 1 is adjusted to 12.0 from 11.3, the aging time 24h set in Example 1 is adjusted to 22h, and in step S1.2 of preparing ternary material A, the sintering temperature 770℃ set in Example 1 is adjusted to 730℃; thus, the particle size D50 of the ternary material A prepared in this comparative example is 10.0μm, and the particle size D50 of the primary particles of the ternary material A is 600nm. In addition to the above differences, the materials and process operations used in this example are strictly consistent with those in Example 1.

[0076] Comparative Example 2

[0077] This comparative example prepares a lithium-ion battery with reference to Example 1. The difference between this comparative example and Example 1 is that in step S1.1 of preparing ternary material A, the concentration of ammonia solution 1.3 mol / L set in Example 1 is adjusted to 1.5 mol / L, the pH of the reaction solution controlled in Example 1 is adjusted to 11.0 from 11.3, and the aging time 24h set in Example 1 is adjusted to 20h; in step S1.2 of preparing ternary material A, the sintering temperature 770℃ set in Example 1 is adjusted to 790℃, and the sintering time 18h set in Example 1 is adjusted to 20h; thus, the particle size D50 of the ternary material A prepared in this comparative example is 18.0μm, and the particle size D50 of the primary particles of the ternary material A is 900nm. In addition to the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0078] Comparative Example 3

[0079] This comparative example prepares a lithium-ion battery with reference to Example 1. The difference between this comparative example and Example 1 is that in step S2.1 of preparing ternary material B, the concentration of ammonia solution 1.3 mol / L set in Example 1 is adjusted to 0.7 mol / L, and the pH of the reaction solution controlled in Example 1 is adjusted to 12.0 from 11.5; in step S2.2 of preparing ternary material B, the sintering temperature 790°C set in Example 1 is adjusted to 730°C, and the sintering time 18h set in Example 1 is adjusted to 15h; thus, the particle size D50 of the ternary material B prepared in this comparative example is 1.0 μm. In addition to the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0080] Comparative Example 4

[0081] This comparative example prepares a lithium-ion battery with reference to Example 1. The difference between this comparative example and Example 1 is that in step S2.1 of preparing ternary material B, the concentration of ammonia solution 1.3 mol / L set in Example 1 is adjusted to 1.8 mol / L, and the pH of the reaction solution controlled in Example 1 is adjusted to 10.8 from 11.5; in step S2.2 of preparing ternary material B, the sintering temperature 790°C set in Example 1 is adjusted to 800°C, and the sintering time 18h set in Example 1 is adjusted to 20h; thus, the particle size D50 of the ternary material B prepared in this comparative example is 7.0 μm. In addition to the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0082] Comparative Example 5

[0083] This comparative example prepares a lithium-ion battery with reference to Example 1. The difference between this comparative example and Example 1 is that the mass ratio of ternary material A to ternary material B in the positive electrode active main material used in this comparative example is 95:5. In addition to the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0084] Comparative Example 6

[0085] This comparative example prepares a lithium-ion battery with reference to Example 1. The difference between this comparative example and Example 1 is that the mass ratio of ternary material A and ternary material B in the positive electrode active main material used in this comparative example is 75:25. In addition to the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0086] Comparative Example 7

[0087] This example prepares a lithium-ion battery with reference to Example 1. The difference between this example and Example 1 is that the ternary material B is polycrystalline particles. In addition to the above differences, the materials and process operations used in this comparative example are strictly consistent with those in Example 1.

[0088] Test Example 1

[0089] 1. Test object:

[0090] The lithium-ion batteries (single cells) prepared in Examples 1 to 9 and Comparative Examples 1 to 7, as well as 2P battery modules and 3P battery modules were used as test objects in this test example. The preparation methods of the 2P battery modules and 3P battery modules are as follows: the single cells are first discharged to 2.5V at 0.2C, and 10 single cells are welded into a 5-series 2-parallel module (2P battery module) using an L-shaped nickel strip, and 15 single cells are welded into a 5-series 3-parallel module (3P battery module) using an L-shaped nickel strip.

[0091] 2. Test items:

[0092] (1) Single cell overcharge test, 2P module overcharge test, 3P module overcharge test: S1. Place single cell, 2P battery module, and 3P battery module at 23±2℃ for 5 minutes; S2. Use a Fluke thermocouple thermometer to monitor the battery surface temperature; S3. Charge at 2C constant current to 10V; S4. Charge for 3 hours or until the voltage stops increasing; S5. After the test is completed, wait for the battery to cool down, record the battery voltage and internal resistance, and observe whether the battery leaks, catches fire, or explodes.

[0093] The evaluation criteria for overcharge test are as follows:

[0094] When a single cell is overcharged, "5 / 5OK" means that 5Pcs of battery cells were tested, and all 5Pcs passed the test (no explosion or fire); when 2P is overcharged, "3 / 3OK" means that 3 modules were tested, and all 3 modules passed the test (no explosion or fire), and "1 / 3OK" means that 3 modules were tested, and 1 module passed the test (no explosion or fire); when 3P is overcharged, "3 / 3OK" means that 3 modules were tested, and all 3 modules passed the test (no explosion or fire), and "0 / 3OK" means that 3 modules were tested, and all 3 modules failed the test.

[0095] 3. Test results:

[0096] Table 1 Performance test results of Examples 1 to 9 and Comparative Examples 1 to 7

[0097]

[0098]

[0099] The test results are shown in Table 1. Comparing the performance test results corresponding to Example 1 and Comparative Examples 1 to 2, it can be found that the overcharge test pass rates of the 2P battery modules and 3P battery modules prepared in Comparative Examples 1 to 2 are significantly lower than those in Example 1. The reason is that, under the same conditions of preparing other materials and operations for the battery, the particle size D50 of the ternary material A used in Comparative Examples 1 to 2 exceeds 12μm to 15μm, and the particle size D50 of the primary particles of the ternary material A exceeds 700nm to 800nm, which makes it difficult for the ternary material B to be fully filled in the voids of the ternary material A, thereby increasing the specific surface area of ​​the ternary positive electrode material NCA and increasing the contact interface between the electrolyte and the ternary positive electrode material NCA, thereby increasing the risk of overcharge side reactions of the ternary positive electrode material and reducing the overcharge test pass rate of the battery module.

[0100] By comparing the performance test results corresponding to Example 1 and Comparative Examples 3 to 4, it can be found that the overcharge test pass rates of the 2P battery modules and 3P battery modules prepared in Comparative Examples 3 to 4 are significantly lower than those in Example 1. The reason is that, under the same conditions of preparing other materials and operations for the battery, the particle size D50 of the ternary material B used in Comparative Examples 3 to 4 exceeds 2μm to 5μm, and the particle size D50 of the primary particles of the ternary material B exceeds 300nm to 500nm, which makes it difficult for the ternary material B to be fully filled in the gaps of the ternary material A, increases the specific surface area of ​​the ternary positive electrode material NCA, and increases the contact interface between the electrolyte and the ternary positive electrode material NCA, thereby increasing the activity of the overcharge side reaction of the ternary positive electrode material and reducing the overcharge test pass rate of the battery module.

[0101] By comparing the performance test results corresponding to Example 1 and Comparative Examples 5-6, it can be found that the overcharge test pass rates of the 2P battery modules and 3P battery modules prepared in Comparative Examples 5-6 are significantly lower than those in Example 1. The reason is that, under the same conditions of other materials and operations for preparing the battery, the mass ratio of ternary material A and ternary material B in the ternary positive electrode material NCA used in Comparative Examples 5-6 does not meet 75:25, resulting in the ternary material B with a smaller particle size being difficult to fully fill in the gaps of the ternary material A with a larger particle size, thereby increasing the specific surface area of ​​the ternary positive electrode material, increasing the contact area between the electrolyte and the ternary positive electrode material, and increasing the risk of overcharge side reactions (thermal runaway, gas production and other safety issues) of the ternary positive electrode material, thereby reducing the overcharge test pass rate of the battery module.

[0102] By comparing the performance test results corresponding to Example 1 and Comparative Example 7, it can be found that the overcharge test pass rate of the 2P battery module and 3P battery module prepared in Comparative Example 7 is significantly lower than that of Example 1. The reason is that under the same conditions of preparing other materials and operations for the battery, the ternary material B used in Comparative Example 7 is a polycrystalline particle, which increases the specific surface area of ​​the ternary positive electrode material NCA, increases the contact area between the electrolyte and the ternary positive material, and its stability is poor, which increases the risk of overcharge side reactions of the ternary positive electrode material, thereby reducing the overcharge test pass rate of the battery module. This shows that Example 1 uses a single-crystal particle ternary material B, which has a small specific surface area and high structural stability, which is conducive to reducing the contact between the ternary positive electrode material NCA and the electrolyte, reducing the overcharge side reaction activity of the ternary positive electrode material NCA, and improving the overcharge stability of the battery. At the same time, the ternary material B has few crystal defects and high space utilization, which can improve the electrochemical performance and overcharge test pass rate of the single cell and battery module prepared therefrom.

[0103] The performance test results of Example 1 are compared with those of Examples 4 to 5. As shown in Table 1, under the same conditions of preparing other materials and operations for the battery, the ternary material B used in Example 4 does not introduce doping elements, and the overcharge test pass rates of the 2P module and 3P module prepared therefrom are slightly lower than those of Examples 1 and 5. This shows that, relative to Example 4, Examples 1 and 5 introduce specific doping elements into the ternary material B, and the doping elements are beneficial to improving the internal element distribution of the ternary material B, improving the structural stability of the ternary material B, and reducing the overcharge side reaction activity of the ternary positive electrode material, thereby improving the overcharge test pass rate and electrochemical performance of the battery module.

[0104] The performance test results of Example 1 are compared with those of Examples 6 to 8. As shown in Table 1, under the same conditions of other materials and operations for preparing the battery, the coating layer provided on the surface of the ternary material A used in Example 6 is thicker, the coating layer provided on the surface of the ternary material A used in Example 7 is thinner, and the surface of the ternary material A used in Example 8 is not provided with a coating layer, and the overcharge test pass rate of the 2P module and 3P module prepared thereby is slightly lower than that of Example 1. This shows that, relative to Examples 6 to 8, Example 1 provides an alumina coating layer of suitable thickness on the surface of the ternary material A, and the alumina coating layer serves as a protective layer, which can reduce the direct contact between the positive electrode material A and the electrolyte, reduce the possibility of overcharge side reactions, and thus improve the overcharge stability of the ternary positive electrode material and the overcharge test pass rate of the battery module.

[0105] The performance test results of Example 1 and Example 9 are compared. As shown in Table 1, under the same conditions of other materials and operations for preparing the battery, the sphericity of the ternary material A used in Example 9 is less than 0.85, and the overcharge test pass rate of the 2P module and 3P module prepared therefrom is slightly lower than that of Example 1. This shows that, compared with Example 9, Example 1 uses a ternary material A with a specific sphericity, which is beneficial to reducing the specific surface area of ​​the ternary positive electrode material, further optimizing its overcharge stability, thereby improving the overcharge test pass rate of the battery module.

[0106] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A ternary positive electrode material, characterized in that: Comprising ternary material A and ternary material B; The particle size D50 of the ternary material A is 12 μm to 15 μm, the ternary material A is a secondary particle, and the particle size D50 of the primary particle of the ternary material A is 700 nm to 800 nm. The particle size D50 of the ternary material B is 2 μm to 5 μm, the ternary material B is a quasi-single crystal particle, and the particle size D50 of the primary particle of the ternary material B is 300 nm to 500 nm; The mass ratio of the ternary material A to the ternary material B is 80-90:10-20.

2. The ternary positive electrode material according to claim 1, characterized in that: The sphericity of the ternary material A is 0.85-0.

95.

3. The ternary positive electrode material according to claim 1, characterized in that: The surface of the ternary material A is provided with a coating layer, the coating layer comprises aluminum oxide, and the aluminum oxide content in the coating layer is not less than 80wt%.

4. The ternary positive electrode material according to claim 3, characterized in that: The coating layer has a thickness of 6 nm to 10 nm.

5. The ternary positive electrode material according to any one of claims 1 to 4, characterized in that: The ternary material A includes nickel cobalt aluminum oxide lithium ternary material.

6. The ternary positive electrode material according to claim 1, characterized in that: The ternary material B includes nickel cobalt aluminum oxide lithium ternary material.

7. The ternary positive electrode material according to claim 6, characterized in that: The chemical formula of the nickel-cobalt-aluminum-lithium ternary material included in the ternary material B is LiNi a Co b Al c M (1-a-b-c) O2, and 0.80≤a≤0.92, 0.062≤b≤0.15, 0.018≤c≤0.05, a+b+c<1, wherein M is a doping element, and the doping element includes at least one of Zr, Mg, and Y.

8. The ternary positive electrode material according to claim 6, characterized in that: The preparation method of the ternary material B comprises the following operations: S1: preparing a cobalt-nickel precursor by a coprecipitation method, and the aging time in the process of preparing the cobalt-nickel precursor is 6 to 10 hours; then sintering the nickel-cobalt precursor at 350 to 450° C. for 4 to 6 hours to obtain nickel-cobalt oxide; S2: adding lithium source material and aluminum source material to the nickel-cobalt oxide, first heating to 450-550° C. and pre-sintering for 6-8 hours, and then heating the resulting mixture to 700-900° C. and sintering for 16-20 hours, thereby obtaining the ternary material B.

9. A lithium ion battery, characterized in that: It comprises a negative electrode sheet and a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode collector and a positive electrode active coating arranged on the surface of the positive electrode collector, and the positive electrode active material contained in the positive electrode active coating comprises the ternary positive electrode material as claimed in any one of claims 1 to 8.

10. A battery module, characterized in that: Comprising the lithium ion battery as claimed in claim 9.

Citation Information

Cited By

  • Coated ternary material doped with different particle sizes, preparation method thereof and battery

    CN120637473A